Prevalence of Salmonella infection in pigeons, canaries and psittacines - GEORGIADES (Γ.Κ. ΓΕΩΡΓΙΑΔΗΣ) G. K.; IORDANIDIS (Π. ΙΟΡΔΑΝΙΔΗΣ) P. (Journal of the Hellenic Veterinary Medical Society, 2018)
During the last decade, 618 pigeons, 182 canaries and 71 pcittacines, from Thessalonica greater area were examined in the Clinic of Poultry Diseases. Post mortem examination was performed in all birds and samples were collected from the liver, spleen, heart and intestine for bacteriological examinations. Blood agar (5% sheep blood), McConkey agar and Selenite broth were used for culturing suspect material. Serological and biochemical tests were performed from colonies grown on agar plates. Salmonella isolates were serotyped at the "Salmonella - Shigella National Research Center" in Athens, Greece. Salmonella was isolated from 53 out of 618 pigeons (8.6%), 33 out of 182 canaries (18.1%) and two out of 71 psittacines (2.8%). S. typhimurium was the most frequently isolated serotype in pigeons (75.5% of isolates), followed by S. enteritidis (11.3%). S. gallinarum and S. hadar (3.8%), as well as S. abony (1.9%) were less frequent. S. typhimurium was also the most frequently isolated serotype in canaries (90.9% of isolates), while S. enteritidis (6.1%) followed. S. infantis and S. gallinarum were each isolated once from psittacines. According to the results, the prevalence of Salmonella infection in the examined birds is considered rather low, while S. typhimurium and S. enteritidis seem to be the most frequent serotypes in these birds.